À la recherche d'une protection efficace contre les inspections abusives de l'État : la Charte québécoise, la Charte canadienne et le Bill of Rights américain - Angers, Lucie (Les Cahiers de droit, 1986)
Many laws in Canada and Québec grant rights of entry to inspectors responsible for looking after the proper operation of structures implemented by the State. From heavily regulated industrials to permit holders and simple citizens, everyone can expect someday to be paid a visit by an inspector. The question arises, however, as to whether the Canadian Charter of Rights and Freedoms and the Québec Charter of Human Rights and Freedoms may be resorted to so as to exercise control over possible abuses resulting from such inspections. These Charters provide security for the person against the State in these areas whether through the right to be protected from unreasonable search and seizure, the right to a private life or to the inviolability of the home. However, the means by which such rights shall be adequately protected are somewhat uncertain. Should this be done by the granting of an administrative warrant issued ex parte as in the United States ? Or by granting the same kind of warrant in the presence of both parties ? The granting of administrative subpoenas also may be a solution to be considered. But for both legal and administrative reasons, it seems that the best control to exercise over these entries would come from drafting well-defined powers of inspection into the law granting them, which would provide an adequate protection of human rights and freedoms.